BECOMING UNGGAN WOMEN: SUBJECTIVITY AND INDIVIDUALITY - Fahmi Marh; Yang Junchu; Selvi Kasman; Hafif HR (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
The women who play music in Nagari Unggan are Minangkabau women. Nagari Unggan women's freedom to play music without men is an anomaly for the Minangkabau indigenous people. Women's liberation becomes something discordant or taboo. His present free existence can be in the form of subordination, and vice versa can be in respect and emancipation. This paper will reveal the free event of the Unggan Woman as becoming or becoming a woman to being Parewa. This research on the narrative of female music players from Calempong Unggan was analyzed using the Deleuze concept; becoming, subjectivity, and individuation occur, but first, the discussion starts from subjectivity and individuation. Meanwhile, Becoming a form of being an Unggan woman is a novelty for Unggan women for their freedom to play calempong. The Woman's narrative was built using qualitative analysis methods through life history ethnography, in the form of reports of women's lives in the Calempong performance room, especially musical players who are experienced in telling their experiences—starting from the narrative of past livesBECOMING PEREMPUAN UNGGAN: SUBJEKTIVITAS DAN INDIVIDUASI AbstrakPerempuan yang bermain musik di Nagari Unggan adalah perempuan Minangkabau. Kebebasan perempuan Nagari Unggan bermain musik tanpa didampingi laki-laki menjadi sesuatu yang anomali bagi masyarakat adat Minangkabau. Kebebasan perempuan itu menjadi sesuatu yang sumbang atau tabu. Keberadaanya sekarang yang bebas itu bisa berupa subordinasi dan sebaliknya bisa berupa penghormatan dan emansipatif. Tulisan ini akan mengungkapkan peristiwa bebas perempuan Unggan itu sebagai becoming atau kemenjadian perempaun menjadi Parewa. Hasil dari penelitian narasi perempuan pemain musik Calempong Unggan ini di analisis menggunakan konsep Deleuze; becoming, subjektivitas dan individuasi, yang terjadi di dalamnya, namun terlebih dahulu diskusi dimulai dari subjektivitas dan individuasi. Sedangkan becoming sebagai bentuk kemenjadian perempuan Unggan menjadi kebaruan perempuan Unggan atas kebebasannya bermain calempong. Narasi Perempuan Ungggan tersebut dibangun dengan metode analisis kualitatif melalui etnografi life history, berupa narasi kehidupan perempuan dalam ruang pertunjukan calempong, terutama pemain musik yang benar-benar berpengalaman menceritakan pengalamannya. Mulai dari narasi kehidupan masa lalu, masa sekarang untuk membangun masa depan perempuan Unggan sebagai pemain musik perempuan yang bebas di Minangkabau.